Quantitative comparison of cortical surface reconstructions from MP2RAGE and multi-echo MPRAGE data at 3 and 7T - Fujimoto, Kyoko; Polimeni, Jonathan R.; van der Kouwe, André J.W.; Reuter, Martin; Kober, Tobias; Benner, Thomas; Fischl, Bruce; Wald, Lawrence L. (NeuroImage (Orlando, Fla.), 2014)
The Magnetization-Prepared 2 Rapid Acquisition Gradient Echo (MP2RAGE) method achieves spatially uniform contrast across the entire brain between gray matter and surrounding white matter tissue and cerebrospinal fluid by rapidly acquiring data at two points during an inversion recovery, and then combining the two volumes so as to cancel out sources of intensity and contrast bias, making it useful for neuroimaging studies at ultrahigh field strengths (≥7T). To quantify the effectiveness of the MP2RAGE method for quantitative morphometric neuroimaging, we performed tissue segmentation and cerebral cortical surface reconstruction of the MP2RAGE data and compared the results with those generated from conventional multi-echo MPRAGE (MEMPRAGE) data across a group of healthy subjects. To do so, we developed a preprocessing scheme for the MP2RAGE image data to allow for automatic cortical segmentation and surface reconstruction using FreeSurfer and analysis methods to compare the positioning of the surface meshes. Using image volumes with 1mm isotropic voxels we found a scan–rescan reproducibility of cortical thickness estimates to be 0.15mm (or 6%) for the MEMPRAGE data and a slightly lower reproducibility of 0.19mm (or 8%) for the MP2RAGE data. We also found that the thickness estimates were systematically smaller in the MP2RAGE data, and that both the interior and exterior cortical boundaries estimated from the MP2RAGE data were consistently positioned within the corresponding boundaries estimated from the MEMPRAGE data. Therefore several measureable differences exist in the appearance of cortical gray matter and its effect on automatic segmentation methods that must be considered when choosing an acquisition or segmentation method for studies requiring cortical surface reconstructions. We propose potential extensions to the MP2RAGE method that may help to reduce or eliminate these discrepancies. •FreeSurfer automatic cortical surface reconstruction is extended to MP2RAGE data.•Reproducibility is quantified for 3T MP2RAGE and ME-MPRAGE surface reconstructions.•A novel analysis of surface discrepancies across imaging methods is introduced.•Systematic differences are found between MP2RAGE and ME-MPRAGE surfaces.•Potential extensions to MP2RAGE are suggested to reduce these discrepancies.